Faktor-faktor yang Memengaruhi Perilaku Konsumen dalam Pembelian Produk Sophie Martin di Kota Makassar - Syaribulan, Syaribulan (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
This study aims to analyze the influence of family factors, economic situation, and lifestyle on the decision to buy Sophie Martin products, and to know which factors give the dominant influence to the decision to buy Sophie Martin products in Makassar. The data were collected using questionnaires distributed to 100 buyers of Sophie Martin products. The data collected were analyzed using descriptive analysis and multiple regression analysis. The results of this study indicate the influence of family, economic situation and lifestyle of purchasing decisions made by consumers of Sophie Martin products in the city of Makassar. This means the marketer, in this case the distributor of Sophie Martin products should consider these three things in marketing their products.